The Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Profitabilitas Dan Arus Kas Terhadap Financial Distress (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Tahun 2020-2021) - Agnes Dewi Anjani; Taswan Taswan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine whether Managerial Ownership, Institutional Ownership, Profitability and Cash Flow affect Financial Distress. The population in this study are 386 companies with secondary data sources derived from the financial reports of manufacturing companies listed on the IDX for 2020-2021. The selection of the research sample used a purposive sampling technique so that the samples obtained were 149 companies. The research method is quantitative. This study applies multivariate analysis by utilizing logistic regression which has non-matrix variables, namely dummy variables (category 0 and category 1). The results of the study show that Managerial Ownership, Institutional Ownership, and Profitability have a negative and significant effect on Financial Distress. Cash flow has a negative and insignificant effect on Financial Distress. Keywords: Managerial Ownership, Institutional Ownership, Profitability, Cash Flow, and Financial Distress.